CCND3 is indispensable for the maintenance of B-cell acute lymphoblastic leukemia - Franz Ketzer; Hend Abdelrasoul; Mona Vogel; Ralf Marienfeld; Markus Müschen; Hassan Jumaa; Thomas Wirth; Alexey Ushmorov (Oncogenesis, 2022)
Abstract The D-type cyclins (CCND1, CCND2, and CCND3) in association with CDK4/6 are known drivers of cell cycle progression. We reported previously that inactivation of FOXO1 confers growth arrest and apoptosis in B-ALL, partially mediated by subsequent depletion of CCND3. Given that previously the canonical MYC target CCND2 has been considered to play the major role in B-ALL proliferation, further investigation of the role of FOXO1 in CCND3 transcription and the role of CCND3 in B-ALL is warranted. In this study, we demonstrated that CCND3 is essential for the proliferation and survival of B-ALL, independent of the mutational background. Respectively, its expression at mRNA level exceeds that of CCND1 and CCND2. Furthermore, we identified FOXO1 as a CCND3-activating transcription factor in B-ALL. By comparing the effects of CCND3 depletion and CDK4/6 inhibition by palbociclib on B-ALL cells harboring different driver mutations, we found that the anti-apoptotic effect of CCND3 is independent of the kinase activity of the CCND3-CDK4/6 complex. Moreover, we found that CCND3 contributes to CDK8 transcription, which in part might explain the anti-apoptotic effect of CCND3. Finally, we found that increased CCND3 expression is associated with the development of resistance to palbociclib. We conclude that CCND3 plays an essential role in the maintenance of B-ALL, regardless of the underlying driver mutation. Moreover, downregulation of CCND3 expression might be superior to inhibition of CDK4/6 kinase activity in terms of B-ALL treatment.